2016
DOI: 10.1163/15685403-00003574
|View full text |Cite
|
Sign up to set email alerts
|

Determination of proximate composition and fatty acid profiles of Astacus leptodactylus Eschscholtz, 1823 in Turkish freshwater resources

Abstract: This research was conducted to evaluate the nutrient content ofAstacus leptodactylusin various populations in the lakes Iznik and Egirdir, as well as in Hirfanlı Dam Lake and Keban Dam Lake, all in Turkey. Crayfish meat yield ranged from a minimum of 11.3% to a maximum of 16.3% of wet weight in specimens from Keban and Iznik, respectively. Meat yield was significantly different, depending on the living environment. The protein content of the meat ofA. leptodactylusranged from 15.4 to 17.5%. The moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Similarly, Stanek et al (2013) indicated no differences between sexes in ∑PUFA contents, however ∑PUFA contents were found similar between spring and summer. Harlioğlu et al (2012) and Dksuz & Mazlum (2016) determined higher ∑PUFA (45.97%, 53.52% respectively) than ∑SFA and ∑MUFA. Also, they detected higher ∑PUFA contents than that of the present study in tail muscle of A. leptodacylus.…”
Section: ∑Mufa Contentsmentioning
confidence: 92%
See 4 more Smart Citations
“…Similarly, Stanek et al (2013) indicated no differences between sexes in ∑PUFA contents, however ∑PUFA contents were found similar between spring and summer. Harlioğlu et al (2012) and Dksuz & Mazlum (2016) determined higher ∑PUFA (45.97%, 53.52% respectively) than ∑SFA and ∑MUFA. Also, they detected higher ∑PUFA contents than that of the present study in tail muscle of A. leptodacylus.…”
Section: ∑Mufa Contentsmentioning
confidence: 92%
“…The cause of this situation may be species and habitat differences. Similarly, Dksuz & Mazlum (2016) determined SFA content as 21.32% in tail muscle A. leptodactylus caught from Egirdir Lake. Harlioğlu et al (2012) reported SFA content as 25.56% in tail muscle of A. leptodactylus caught from Lake Keban Dam.…”
Section: ∑Mufa Contentsmentioning
confidence: 93%
See 3 more Smart Citations